2020
DOI: 10.1177/2277975220941946
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Annual Reports and Operating Performance of Indian Banking Companies

Abstract: Existing literature focuses on the evaluation of the readability of annual reports of non-banking companies. However, banking companies’ opaque nature and a double motivation to abuse accounting discretion requires a separate study on the readability of banks’ annual reports in association with their performance. We, therefore, attempt to explore firm performance and readability of banking firms’ annual reports in India. Net interest margin (NIM) and Fog Index are used as performance and readability variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…Furthermore, they underlined the existence of a positive relationship between CSR performance and the level of readability. Jayasree and Shette (2021) found that the section “Management discussion and analysis” of the annual reports of Indian banks is difficult to read. They also found a negative influence of financial performance on the level of readability.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Furthermore, they underlined the existence of a positive relationship between CSR performance and the level of readability. Jayasree and Shette (2021) found that the section “Management discussion and analysis” of the annual reports of Indian banks is difficult to read. They also found a negative influence of financial performance on the level of readability.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Therefore, protects the interests of the shareholders and serves as the best means of communication which improves the relationship between the managers and the stakeholders. Better the agent-principal relationship, decreasing agency cost, hence increasing the firm profitability (Bryan, 1997;Brown and Tucker, 2011;Cole and Jones, 2014;Jayasree and Shette, 2020). However, in certain studies, the relationship is found negative because managers use an impression management strategy to attract potential investors and avoid any questions from the existing shareholders.…”
Section: Mdanda In Indiamentioning
confidence: 99%
“…‫المالية؛‬ ‫تقاريرها‬ ‫تعقد‬ ‫ومدى‬ ‫للمنشأة‬ ‫المالي‬ ‫األداء‬ ‫بين‬ ‫عكسية‬ ‫عالقة‬ ‫وجود‬ ‫إلى‬ ‫الدراسات‬ ‫تلك‬ ‫غالبية‬ ‫توصلت‬ ‫وقد‬ ‫هذا،‬ ‫القوي‬ ‫المالي‬ ‫األداء‬ ‫ذات‬ ‫المنشأة‬ ‫من‬ ‫ًا‬ ‫تعقد‬ ‫أكثر‬ ‫تقارير‬ ‫تصدر‬ ‫الضعيف‬ ‫المالي‬ ‫األداء‬ ‫ذات‬ ‫المنشأة‬ ‫أن‬ ‫أي‬ (Subramanian, Insley, & Blackwell, 1993;Smith & Taffler, 2000;Li, 2008;Bloomfield, 2008;Hrasky & Smith, 2008;Smith, Dong, & Ren, 2011;Dempsey, Harrison, Luchtenberg, & Seiler, 2012;Abdul Rahman, 2014;Lo, Ramos, & Rogo, 2017;Asay, Libby, & Rennekamp, 2018;Hassan, Abba s, & Garas, 2019;Gu & Dodoo, 2020;Jayasree & Shette , 2021) . (Courtis, 1995;Sydserff & Weetman, 2002;Rutherford, 2003;Smith, Jamil, & Johari, 2006;Prince, 2017;Soepriyanto, Tjokroaminoto, & Zudana, 2021) .…”
Section: ‫على‬ ‫تؤثر‬ ‫القراءة‬unclassified
“…‫فقد‬ ‫السابق،‬ ‫االدعاء‬ ‫مع‬ ‫ا‬ ً ‫واتساق‬ ‫قدمت‬ ‫اإلف‬ ‫أن‬ ‫على‬ ً ‫دليال‬ ‫الحديثة‬ ‫األدبيات‬ ‫بعض‬ ‫المعقدة‬ ‫السردية‬ ‫المحاسبية‬ ‫صاحات‬ ‫المنشأة‬ ‫بأرباح‬ ‫ًا‬ ‫سلب‬ ‫األحوال‬ ‫أغلب‬ ‫في‬ ‫ترتبط‬ (Davies, 2007;Souza, Rissatti, Rover, & Borba, 2019;The Association of Chartered Certified Accountants, 2009;Mutiso & Kamau, 2013;Oberholster, Koornhof, & Vorster, 2015;Sukotjo & Soenarno, 2018) . (Subramanian, Insley, & Blackwell, 1993;Courtis, 1995;Smith & Taffler, 2000;Sydserff & Weetman, 2002;Rutherford, 2003;Smith, Jamil, & Johari, 2006;Li, 2008;Bloomfield, 2008;Hrasky & Smith, 2008;Smith, Dong, & Ren, 2011;Dempsey, Harrison, Luchtenberg, & Seiler, 2012;Abdul Rahman, 2014;Lo, Ramos, & Rogo, 2017;Prince, 2017;Asay, Libby, & Rennekamp, 2018;Hassan, Abbas, & Garas, 2019;Gu & Dodoo, 2020;Jayasree & Shette , 2021;Soepriyanto, Tjokroaminoto, & Zudana, 2021) .…”
unclassified